Utility of Enterocheck as a Rapid Diagnostic Tool for Typhoid Fever in Children - K.C., Rajesh; Karn, Subhash Lal; Gupta, Murli Manohar; Mahaseth, Sameer (Journal of Nepalgunj Medical College, 2025)
Introduction: Typhoid is a major cause of morbidity and mortality worldwide. The annual incidence in the Indian subcontinent including Nepal has approximately 6 million cases each year. Blood culture is the gold standard for diagnosis but it requires well- equipped laboratory and trained staffs. Enterocheck is a rapid immunoassay which detects IgM antibodies to lipopolysaccharide specific to S. typhi in human blood. It is an alternative test which detects early infection. Aims: To study the sensitivity and specificity of Enterocheck for diagnosing typhoid. Methods: The cross-sectional study was carried out in the department of Pediatrics and Microbiology at Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke, from August 2023 to February 2024, on 145 children, above 6 months- 15 years of age, who presented with fever for more than 72 hours and other features (e.g. headache, abdominal pain, vomiting, diarrhea or constipation, hepatomegaly, splenomegaly) suggestive of typhoid fever. Blood culture was done by aseptic standard method and Enterocheck was done according to the manufacturer’s instructions. Results: Of the 145 cases, 17 (11.7%) had blood cultures positive for S. typhi and 29 (20%) were positive using Enterocheck. Male: female ratio was 2.15:1 and was most common in the age group 5 to 10 years (51.03%). The sensitivity and specificity of Enterocheck was 88.23% and 89.06% respectively (p-value<0.01). Conclusion: Enterocheck test was easy to perform and did not require special equipment or trained staffs. It had high sensitivity and specificity. Thus, it can be used as an alternative to blood culture for diagnosis of typhoid fever.